Mr. coffee, i had a dream about you last night! / Maisurasalima Binti Mohamed @ Mohd Nor - Mohamed @ Mohd Nor, Maisurasalima (Collage of Creative Arts, 2022)
For most of us, coffee is linked with beginning the day, gaining energy to work hard, thinking clearly, and dreaming. Coffee may be used as coloring to decorate and color textile surfaces besides consuming it. Coffee as natural dye comes in a variety of hues other than the traditional brown. By adding different mordant, it can range from dark brown, greenish, or gray. My collection of art to wear is made using calico as the base fabric. The construction of these wearables are highly textured from the combination of various resist application and fabric manipulation technique. In addition, a four meter naturally dyed batik fabric was also explored to understand the effects and process involved in making a fully eco batik textile.